Growth hormone treatment for short stature associated with duplication of the NSD1 Sotos syndrome gene. (5th March 2021) - Bernhardt, Isaac T; Gunn, Alistair J; Carter, Philippa J
Summary: NSD1 deletions are associated with the Sotos syndrome, a syndrome of overgrowth in childhood without evidence of endocrine disturbance. Duplications involving the NSD1 gene have been reported to be associated with a 'reverse Sotos syndrome' phenotype, characterised by short stature, microcephaly, dysmorphic features and developmental delay. A 2-year-old girl with short stature, dysmorphic features and developmental delay was found to have duplication of 5q32.2–5q32.3, which includes the NSD1 gene. Growth hormone stimulation testing was normal. Growth hormone therapy was initiated at 5 years of age due to severe short stature and growth failure, with height 3.35 standard deviations (SDS) below the median. Growth velocity increased markedly, by +4.91 SDS in the first year of treatment. At the time of last follow-up at 9 years and 11 months, she had achieved a height within 1 SDS of the median. This is the first report of growth hormone therapy for the short stature associated with duplication of the NSD1 gene, showing that despite normal pituitary function, exogenous growth hormone can dramatically improve linear growth. Learning points: Sotos syndrome is a disorder of childhood overgrowth caused by NSD1 deletions. Duplications involving NSD1 cause a 'reverse Sotos syndrome' phenotype characterised by short stature and microcephaly. The contrasting phenotypes of NSD1 deletions and duplications suggest a dose effect. Stimulated growth hormone secretion is normal in children with NSD1 deletions and duplications. Growth hormone therapy can be very effective in children with NSD1 duplications, comparable to the response seen in severe growth hormone deficiency.